Phytosociology of a natural fragment of the floodplain forest in the Lower Tapajós River, Brazil - dos Santos Vieira, Diego; Romarco de Oliveira, Marcio Leles; Vasconcelos Gama, João Ricardo; Mendonça Machado, Evandro Luiz; Bastos Gӧrgens Eric; Oliveira Lafetá, Bruno; Silva Garcia, Josinei (BOSQUE, 2017)
The aim of this study was to describe the floristic, structure and spatial pattern of species occurring in a natural fragment of the floodplain forest in the lower Tapajós River, Pará. Three hundred and eight contiguous sampling unities of 100 m² were installed, comprising a sampling area of 3.08 ha. In each plot, all individuals with DBH (diameter at breast height of 1.30 cm) equal to or higher than 10 cm were measured, identified, and referenced in Cartesian coordinates (X, Y). The analyses of the diversity and spatial pattern were performed using the Shannon-Weaver index and the Ripley’s K function, respectively. There were 1,022 individuals surveyed, including 64 tree species and 33 families. The diversity recorded was 3.03; the total density was determined to be 331.8 individuals ha-1 and basal area of 16.10 m2 ha-1. The species of high ecological value were Campsiandra laurifolia, Hevea brasiliensis, Glicoxylon pedicellatum, Tetragastris altissima, Vantanea parviflora and Mabea caudata. The diametric distribution of the community and species, except for Hevea brasiliensis, behaved as expected for uneven-aged forests, and presented an exponential distribution with an inverted J form. The community spatial pattern showed variations depending on the considered distance, however there was a predominance of aggregated distribution. The spatial patterns detected on the species were: I - partially aggregated and random for Vantanea parviflora species, II - completely aggregated to the Hevea brasiliensis and Glicoxylon pedicellatum species, and III - predominantly aggregated to Campsiandra laurifolia, Tetragastris altissima and Mabea caudata.